2001
DOI: 10.1111/1467-6494.694155
|View full text |Cite
|
Sign up to set email alerts
|

The Non‐Evaluative Circumplex of Personality Adjectives

Abstract: In judgments about personality, descriptive and evaluative aspects are ordinarily combined; separating them can be important both theoretically and practically. Study 1 showed that two similar descriptive factors can be found in analyses of personality terms, selected independently in English and in German and using different methods to control for evaluation. The factors relate to two pairs of independent axes suggested by previous work: Assertive-Unassertive and Tight-Loose, or alternatively, Interactional O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
(104 reference statements)
1
39
0
2
Order By: Relevance
“…Trumpet players were rated as tougher than fiautists or violin players. To the extent that toughness or emotional stability is related to extraversion and dominance (Saucier, Ostendorf, & Peabody, 2001), these results may be considered in line with previous studies (Cribb & Gregory, 1999). However, violin players were rated as more egocentric than fiautists or trumpet players.…”
Section: Discussionsupporting
confidence: 84%
“…Trumpet players were rated as tougher than fiautists or violin players. To the extent that toughness or emotional stability is related to extraversion and dominance (Saucier, Ostendorf, & Peabody, 2001), these results may be considered in line with previous studies (Cribb & Gregory, 1999). However, violin players were rated as more egocentric than fiautists or trumpet players.…”
Section: Discussionsupporting
confidence: 84%
“…It includes a 20th category (II-X-gr) added to complete the circle that is central to the figure and interpreted as "Expressive Involvement" on the basis of patterns of correlations with questionnaire scales. The circle in the figure corresponds closely to that defined in the double-cone model of Peabody and Goldberg (1989) and the Non-Evaluative Personality Circumplex of Saucier, Ostendorf, and Peabody (2001). Clusters adjacent to each other in the figure contained adjectives that had their highest loading on the same factor in two of the three models and, thus, that in new studies are more likely to fall on the same factor than are those more distant.…”
Section: Do Lexical Studies Lead To Inconsistent Results?mentioning
confidence: 81%
“…Trobst (2000) placed the IAS scales within the space defined by her Support Actions Scales Circumplex scales (and vice versa) and concluded that the two measures overlapped on the horizontal axis (LM-DE). Saucier, Ostendorf, and Peabody (2001) found the IAS and their Non-Evaluative Personality Circumplex shared the vertical axis (PA-HI). To assess the validity of the interpersonal transaction cycle, Wagner, Kiesler, and Schmidt (1995) conducted a PCA on Impact Message Inventory (Kiesler, 1987) and Inventory of Interpersonal Problems (Alden et al, 1990) and found a structural convergence of these two circumplex measures on a common two-dimensional space.…”
Section: On the Relation Between Affect And Personalitymentioning
confidence: 96%